Qualified Legislator’s Silence: Problem of Recognition - Yu. I. Chalyy (Bulletin of Kharkiv National University of Internal Affairs)
The problem of developing the ways of recognition of the qualified silence of the legislator has been studied. It has been stated that the “qualified silence of the legislator” is underdeveloped category of law, especially regarding the ways of recognizing such specific legislative silence within the norms of law. This problem has become more urgent due to the revival of case law in Ukraine on the application of the analogy of law and the analogy of legislation. While applying these techniques, overcoming the gaps of civil law, the courts often identify the relevant gaps of the legislation with the qualified silence of the legislator, which is a major shortcoming. Solution of this problem will allow the courts to better identify the qualified silence of the legislator in the law norms.